The logic of attraction: exploring the institutional complexity of job preferences - Petry, Tanja; Treisch, Corinna; Bullinger, Bernadette (Emerald Group Holdings Ltd., 2020)
Purpose: Applying the institutional logics perspective to applicant attraction,this study investigates the level of uniformity among preferences for consulting job attributes associated with the institutional logics of the corporation,the profession and the family,and tests for the influence of anticipatory socialization differences. Design/methodology/approach: The study uses a discrete choice experiment with 232 business students. A hierarchical Bayes approach to conjoint analysis uncovers part-worth heterogeneity and allows for subsequent cluster and regression analysis of the choice data. Findings: The findings identify a dominant job-oriented preference type and a minor career-oriented preference type. Anticipatory socialization through personal prior work experience and the occupation of friends decreases adherence to the logic of profession and increases the relevance of the family logic. The parents' occupation has only a minimal influence on preferences. Practical implications: The study provides attribute-based recommendations on how professional service firms can effectively address the complex expectations of potential applicants in their job ads for an entry position and underlines the role of intra-generational reference groups as important anticipatory socializers. Originality/value: By testing individual socialization effects at the pre-hire stage and beyond the organizational level,the study fills a void in both the recruitment and the institutional literature. © 2020,Tanja Petry,Corinna Treisch and Bernadette Bullinger.
Keywords: Anticipatory socialization; Conjoint analysis; Individual differences; Institutional logics; Job pursuit intentions; ODS 8 - Trabajo decente y crecimiento económico